Portoamides A and B are mitochondrial toxins and induce cytotoxicity on the proliferative cell layer of in vitro microtumours. (February 2020) - Sousa, Maria Lígia; Ribeiro, Tiago; Vasconcelos, Vítor; Linder, Stig; Urbatzka, Ralph
Abstract: Cyanobacteria are known to produce many toxins and other secondary metabolites. The study of their specific mode of action may reveal the biotechnological potential of such compounds. Portoamides A and B (PAB ) are cyclic peptides isolated from the cyanobacteria Phormidium sp. due to their growth repression effect on microalgae and were shown to be cytotoxic against certain cancer cell lines. In the present work, viability was assessed on HCT116 colon cancer cells grown as monolayer culture and as multicellular spheroids (MTS), non-carcinogenic cells and on zebrafish larvae. HCT116 cells and epithelial RPE-1 hTERT cells showed very similar degrees of sensitivities to PAB . PAB were able to penetrate the MTS, showing a four-fold high IC50 compared to monolayer cultures. The toxicity of PAB was similar at 4 °C and 37 °C suggesting energy-independent uptake. PAB exposure decreased ATP production, mitochondrial maximal respiration rates and induced mitochondrial membrane hyperpolarization. PAB induced general organelle stress response, indicated by an increase of the mitochondrial damage sensor PINK-1, and of phosphorylation of eIF2α, characteristic for endoplasmic reticulum stress. In summary, these findings show general toxicity of PAB on immortalized cells, cancer cells and zebrafish embryos, likely due to mitochondrial toxicity. Graphical abstract: Image 1 Highlights: Colon carcinoma cells and normal epithelial cells demonstrated similar sensitivity to portoamides. Zebrafish larvae were strongly affected by portoamides. PAB had prominent cytotoxic effects on the prolific outer layer of spheroids. Toxicity of PAB is suggested via energy-independent uptake. PAB induced mitochondrial toxicity (ATP production, respiration rates, mitochondrial membrane hyperpolarization).